Simulation and Properties of the Wide-Band Hybrid Slow-Wave System - Daškevičius, V.; Skudutis, J.; Katkevičius, A.; Štaras, S. (Elektronika ir Elektrotechnika, 2010)
The meander slow-wave system with bended and formed lateral parts of meander electrodes is considered. The system has features of meander and helical systems and can be considered as the hybrid helical-meander-helical (HMH) system. The multiconductor line method and the CST Microwave Studio software system are used for simulation of the HMH system. Expressions for retardation factor and input impedance of the systems are derived using the multiconductor line method. The CST Microwave Studio software is used for calculation of characteristic impedance, retardation factor versus frequency and transfer function of the signal path containing meander and HMH systems. According to results of simulation, using formed meander electrodes, we can considerably increase characteristic impedance and ensure the wide-pass-band of the signal path.